An interesting presentation of a sacrococcygel teratoma with an associated neuroendocrine tumor: A case report - Daniel Krebs; Richard S. Herman; Barry Berch (Elsevier, 2015)
Teratomas are the most frequently occurring germ cell tumors, with 45-65 percent occurring in the sacrococcygeal region [1]. The case presented below involves a newborn male with a malignant sacrococcygeal teratoma and a number of congenital deformities including a left lower extremity amputation, an absent left kidney, hypoplastic and absent left hemipelvis musculature. After excision of the teratoma and subsequent chemotherapy treatment, the patient returned with a persistent abnormal soft tissue, containing persistent malignant elements around the left femur, suspicious for a neuroendocrine tumor. This case shows a rare association between two exceedingly uncommon malignancies.